Utilization of Visual Media in Overcoming Reading Delays Among 2nd Grade Elementary School Students: Pemanfaatan Media Gambar dalam Mengatasi Keterlambatan Membaca pada Siswa Kelas 2 Sekolah Dasar - Ahmad, Ahmad; Ridwan Andi Mattoliang; Nur Rahmi; Dedi Harianto; Kemalasari, Andi Anggi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Reading skills are fundamental abilities that are essential in the learning process, especially for elementary school students. However, reading delays remain one of the main problems faced by 2nd-grade students at UPT SBF SD Negeri Panaikang III. This community service program aims to address reading delays through the utilization of visual media as a teaching aid. The program is implemented in stages, including problem identification, planning, activity execution, evaluation, and follow-up actions. Interventions are carried out using visual media, such as illustrated flashcards, posters, and picture storybooks, designed to enhance students' interest, motivation, and reading skills. Mentoring activities are conducted individually and in small groups, involving teachers and parents to support the learning process. Evaluations are conducted through direct observation, discussions with teachers, and interviews with students and parents. The program results indicate that the use of visual media significantly improves students' reading abilities. In conclusion, the utilization of visual media is effective in addressing reading delays among 2nd-grade students and provides positive impacts on their psychological and social aspects. It is recommended that this method be implemented sustainably and further developed to improve the quality of reading instruction at the elementary school level through collaboration between schools, teachers, and parents. ABSTRAK Keterampilan membaca merupakan kemampuan dasar yang sangat penting dalam proses pembelajaran, terutama bagi siswa sekolah dasar. Namun, keterlambatan membaca masih menjadi salah satu permasalahan utama yang dihadapi oleh siswa kelas 2 UPT SBF SD Negeri Panaikang III. Program pengabdian masyarakat ini bertujuan untuk mengatasi keterlambatan membaca melalui pemanfaatan media gambar sebagai alat bantu pembelajaran. Pelaksanaan program dilakukan melalui tahapan identifikasi masalah, penyusunan rencana, pelaksanaan kegiatan, serta evaluasi dan tindak lanjut. Intervensi dilakukan dengan menggunakan  media gambar, seperti kartu bergambar, poster, dan buku cerita bergambar, yang dirancang untuk meningkatkan minat, motivasi, dan kemampuan membaca siswa. Kegiatan pendampingan dilaksanakan secara individual maupun kelompok kecil, dengan melibatkan guru dan orang tua dalam mendukung proses pembelajaran. Evaluasi dilakukan melalui pengamatan langsung, diskusi dengan guru, dan wawancara dengan siswa serta orang tua. Hasil program menunjukkan bahwa penggunaan media gambar mampu meningkatkan kemampuan membaca siswa secara signifikan. Kesimpulannya, pemanfaatan media gambar efektif dalam mengatasi keterlambatan membaca siswa kelas 2, serta memberikan dampak positif terhadap aspek psikologis dan sosial siswa. Disarankan agar metode ini diterapkan secara berkelanjutan, serta dikembangkan untuk meningkatkan kualitas pembelajaran membaca di tingkat sekolah dasar, dengan sinergi antara sekolah, guru, dan orang tua.